2009
DOI: 10.1211/jpp/61.06.0009
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of JBP485 on concanavalin A-induced liver injury in mice

Abstract: Objectives Cyclo-trans-4-L-hydroxyprolyl-L-serine (JBP485) was first isolated from Laennec (hydrolysate of human placenta). We thought it valuable to clarify the antihepatitis molecular mechanism of JBP485 to develop a new oral anti-hepatitis drug. Methods We investigated the hepatoprotective effect of JBP485 on immune-mediated, concanavalin A (Con A)-induced liver injury in mice. Mice were administered JBP485 before and after injection of Con A (10 mg/kg). Eight hours after Con A, the cytosolic enzyme activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…7B). JBP485 is a dipeptide (Liu et al, 2000) with antihepatitis and gastrointestinal protective effects (Liu et al, 1998;Wu et al, 2008) that was first isolated from Laennec (Yang et al, 2009), a substrate of OAT1 and OAT3 (Zhang et al, 2010). We found that PCG, probenecid, JBP485, and aspirin inhibited the uptake of cilostazol in a concentration-dependent manner (Fig.…”
Section: Mechanism Of Ddi Between Cilostazol and Aspirin Or Probenecimentioning
confidence: 64%
“…7B). JBP485 is a dipeptide (Liu et al, 2000) with antihepatitis and gastrointestinal protective effects (Liu et al, 1998;Wu et al, 2008) that was first isolated from Laennec (Yang et al, 2009), a substrate of OAT1 and OAT3 (Zhang et al, 2010). We found that PCG, probenecid, JBP485, and aspirin inhibited the uptake of cilostazol in a concentration-dependent manner (Fig.…”
Section: Mechanism Of Ddi Between Cilostazol and Aspirin Or Probenecimentioning
confidence: 64%
“…1) is a dipeptide first isolated from Laennec [6]. Laennec is a proprietary product made from the hydrolysate of human placenta [7]. JBP485 has been reported to have several biological properties.…”
Section: Ivyspringmentioning
confidence: 99%
“…JBP485 has been reported to have several biological properties. In concanavalin A (Con A)-induced liver injury mouse model, administration of JBP485 reduced hepatic damage, such as increases in tumor necrosis factor (TNF)-α and intercellular adhesion molecule-1 expression and apoptosis in the liver [7]. Also, administration of JBP485 to rats improved gentamicin-induced acute renal failure [8].…”
Section: Ivyspringmentioning
confidence: 99%
“…1C) are also dipeptides first isolated from Laennec, which are proprietary products made from the hydrolysate of human placenta in Japan, and have been synthesized by chemical means. Animal experiments have indicated that JBP485 and JBP923 could protect liver after oral administration of JBP485 and JBP923 (Liu et al, 1998(Liu et al, , 2000Sun et al, 2009;Terada et al, 1997;Wang et al, 2011aWang et al, , 2011bWu et al, 2008;Yang et al, 2009;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%